Study Modules for Calculus-Based General Physics. [Includes Modules 38-40 Optical Instruments; Diffraction; and Alternating Current Circuits] - Nebraska Univ., Lincoln; Fuller, Robert G.; Nebraska Univ., Lincoln ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This is part of a series of 42 Calculus Based Physics (CBP) modules totaling about 1,000 pages. The modules include study guides, practice tests, and mastery tests for a full-year individualized course in calculus-based physics based on the Personalized System of Instruction (PSI). The units are not intended to be used without outside materials; references to specific sections in four elementary physics textbooks appear in the modules. Specific modules included in this document are: Module 38--Optical Instruments, Module 39--Diffraction, and Module 40--Alternating Current Circuits. (CP)
Availability: University of Nebraska, CBP Workshop, Behlen Laboratory of Physics, Lincoln, Nebraska 68588 (entire set of 42 modules, $15.00).
Sponsoring Agency: National Science Foundation, Washington, DC.
ERIC Note: Prepared at a College Faculty Workshop (University of Colorado, Boulder, June 23-July 11, 1975); Directions for the CBP modules are found in SE 020 448; Related documents are SE 020 449-461.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Calculus; College Science; Course Descriptions; Electricity; Higher Education; Individualized Instruction; Instructional Materials; Optics; Physics; Programed Instruction; Science Education; Undergraduate Study; Personalized System of Instruction; Keller Plan; Guides, General